Snuff use and smoking in Finnish Olympic athletes - Alaranta, A.; Alaranta, H.; Patja, K.; Palmu, P.; Prättälä, R.; Martelin, T.; Helenius, I. (International Journal of Sports Medicine, 2006)
This study aimed to assess the prevalence of smoking and snuff use in Finnish elite athletes. Of all the athletes (n = 494) financially supported by the National Olympic Committee, 446 completed a structured questionnaire (response rate 90.3 %) in 2002. A control group (n = 1504, response rate 80.2 %) comprised an age-matched sample from the population-based sample collected by the National Public Health Institute. Any smoking was reported by 11.4 % of the athletes (3.6 % daily and 7.8 % occasionally) and by 38.3 % of the controls (28.1 % and 10.2 %). After adjusting for age, sex, and education, OR (95 % CI) for any smoking was highest 0.42 (0.23 - 0.77) for athletes in skill-based events and lowest 0.06 (0.02 - 0.17) for endurance athletes as compared with controls. Snuff use was reported by 24.6 % of the athletes (9.6 % daily and 15.0 % occasionally) and by 3.7 % of the controls (1.8 % and 1.9 %). The adjusted OR (95 % CI) for any snuff use was highest 15.6 (9.55 - 25.6) for team-sport athletes and lowest 3.33 (1.54 - 7.21) for endurance athletes as compared with controls. Although snuff use in the general female population is rare, also female athletes did use snuff. Though prevalence of daily smoking among athletes was one-seventh of the respective figure for the general population, prevalence of daily snuff use was five-fold that of controls. Tobacco free elite athletes are valuable in health counselling because athletes are considered role models influencing their peers and the sport. Sport associations are challenged to ban all forms of tobacco.